2011
DOI: 10.1021/nn202868a
|View full text |Cite
|
Sign up to set email alerts
|

Light-Weight Flexible Carbon Nanotube Based Organic Composites with Large Thermoelectric Power Factors

Abstract: Typical organic materials have low thermal conductivities that are best suited to thermoelectrics, but their poor electrical properties with strong adverse correlations have prevented them from being feasible candidates. Our composites, containing single-wall carbon nanotubes, poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) and/or polyvinyl acetate, show thermopowers weakly correlated with electrical conductivities, resulting in large thermoelectric power factors in the in-plane direction of the compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
355
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(376 citation statements)
references
References 44 publications
3
355
5
1
Order By: Relevance
“…[ 12,13 ] Interestingly, the thermal conductivity of bulk polymers as well as conjugated macromolecules can be tuned by controlling molecular orientation. [14][15][16] In order to increase the modest electrical conductivity of polymers, a number of strategies have been proposed, including careful doping, [ 4,11,[17][18][19][20][21] making composites of polymers with conductive fi llers such as CNTs, [22][23][24] or fabricating multilayer composite A broad range of organic electronic applications rely on the availability of both p-and n-type organic semiconductors, and the possibility to deposit them as sequential layers or to form spatial patterns. Examples include transport layers in diodes (OLEDs, photovoltaics, etc.…”
Section: Doi: 101002/adma201505521mentioning
confidence: 99%
“…[ 12,13 ] Interestingly, the thermal conductivity of bulk polymers as well as conjugated macromolecules can be tuned by controlling molecular orientation. [14][15][16] In order to increase the modest electrical conductivity of polymers, a number of strategies have been proposed, including careful doping, [ 4,11,[17][18][19][20][21] making composites of polymers with conductive fi llers such as CNTs, [22][23][24] or fabricating multilayer composite A broad range of organic electronic applications rely on the availability of both p-and n-type organic semiconductors, and the possibility to deposit them as sequential layers or to form spatial patterns. Examples include transport layers in diodes (OLEDs, photovoltaics, etc.…”
Section: Doi: 101002/adma201505521mentioning
confidence: 99%
“…Previous studies on the TE properties of conducting polymers and their composites revealed that the use of template induction with inorganic nanoparticles (for example, carbon nanotubes, graphene, metal nanowires) increased the degree of ordering of polymer molecular arrangements and therefore improved σ and S, [11][12][13][14][15][16] but a clear explanation for the intrinsic effect of the molecular structure on electron transport is still lacking. The electron transport in a conducting polymer composite containing an inorganic dispersion phase is complex because multiple factors may influence the transport process in diverse ways.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric materials based on single-walled carbon nanotubes (SWNTs) are the most striking candidates for future flexible power generators. 13 Their degree of energy conversion is usually expressed as a dimensionless figure of merit, ZT = ¡ 2 ·T/¬, where ¡ is the Seebeck coefficient, · is electrical conductivity, T is temperature, and ¬ is thermal conductivity. SWNTs possess high electrical conductivity and structural flexibility but have the disadvantages of a small Seebeck coefficient and high thermal conductivity.…”
mentioning
confidence: 99%
“…In most cases, conducting polymers serve as efficient electrical conductors, and insulating polymers are useful for low thermal conductivity, which thus enhance ZT. 13,14 On the other hand, a rational approach for improving the Seebeck coefficient of SWNTs is still a challenging subject. Because of the trade-off relationship between conductivity and the Seebeck coefficient, the Seebeck coefficient was usually sacrificed for increased electrical conductivity.…”
mentioning
confidence: 99%